Cryptic Female Choice in Arthropods 2015
DOI: 10.1007/978-3-319-17894-3_3
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic Female Choice Within the Genus Argiope: A Comparative Approach

Abstract: The orb-web spider genus Argiope (Araneae) offers an excellent opportunity to detect cryptic female choice and to identify the species-specific traits that might lead to its evolution and maintenance. All studied species of the genus Argiope are characterized by low male mating rates. While males of some species are strictly mono-or bigynous, others plastically switch between these two strategies. All studied species show sexual cannibalism during copulation. Generally, males die after their second copulation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…The studies mentioned above have focused on endosymbionts alone within a single family of spiders. It has not yet been investigated whether there are intraspecific differences in the total (endosymbiont and non-endosymbiont) microbial community between different spider populations, the composition of the microbiome in certain tissue types, or whether there is vertical transmission of the microbiome in spiders.Argiope bruennichi (Scopoli, 1772), an orb-weaving spider with a Palearctic distribution [47], is an ideal candidate for a pioneering microbiome study given the wealth of knowledge that exists on the biology of the species and the genus Argiope [48]. It has been the subject of many studies due to a number of interesting traits, such as sexual dimorphism and sexual cannibalism (i.e., [49][50][51]), and its recent and rapid range expansion within Europe [47,[52][53][54][55].…”
mentioning
confidence: 99%
“…The studies mentioned above have focused on endosymbionts alone within a single family of spiders. It has not yet been investigated whether there are intraspecific differences in the total (endosymbiont and non-endosymbiont) microbial community between different spider populations, the composition of the microbiome in certain tissue types, or whether there is vertical transmission of the microbiome in spiders.Argiope bruennichi (Scopoli, 1772), an orb-weaving spider with a Palearctic distribution [47], is an ideal candidate for a pioneering microbiome study given the wealth of knowledge that exists on the biology of the species and the genus Argiope [48]. It has been the subject of many studies due to a number of interesting traits, such as sexual dimorphism and sexual cannibalism (i.e., [49][50][51]), and its recent and rapid range expansion within Europe [47,[52][53][54][55].…”
mentioning
confidence: 99%
“…Although very little is known, similar cryptic female mechanisms have been described in spider species. In the genus, Physocyclus females would eject males' sperm depending on their copulatory courtship performance (Peretti & Eberhard, ), or among the spider genera Lactrodectus , Leucage and Argiope it seems possible that females can bias fertilisation of their eggs by controlling the mating plug formation (Aisenberg, Barrantes, & Eberhard, ; Andrade & MacLeod, ; Schneider, Uhl, & Herberstein, ). Beyond the mechanisms, it has been also suggested that female spiders can selectively store sperm of courting males (Schneider & Lesmono, ), cannibalised males (Herberstein et al., ) and gift‐giving males (Albo, Bilde, & Uhl, ).…”
Section: Discussionmentioning
confidence: 99%
“…The latter requires that the females add to the male's paste a liquid that she secretes, and females may be swayed to cooperate with the male in this manner by his copulatory courtship (Aisenberg and Eberhard 2009;Aisenberg et al 2015). Similarly, in Argiope keyserlingi orb web spiders, all the female has to do is allow the male sufficient time to break off and lodge a fragment of his genitalia in her genital opening in a position that will make an effective plug; if she ends the copulation earlier, fragments of the male's genitalia are not lodged well and do not make an effective plug (Herbertstein et al 2012;Schneider et al 2015).…”
Section: Females Cooperate With the Male To Form A Copulatory Plugmentioning
confidence: 96%